(untitled) (Tikrit Journal of Veterinary Science, 2023)
The place where the experiment was conducted was the animal house. The duration was 30 days, the number of birds was 60, and their weights ranged from 75 grams - 110 grams. Also, the dose of gabapentin used was 990 mg/kg. The aim of this study was to know the effect of oxidative stress induced by hydrogen peroxide on the drug response to gabapentin and to compare this effect with normal chicks, as well as to know the effect of oxidative stress on neurotransmitters (kappa and glutamate), and antioxidants (malonaldehyde and glutathione). Giving hydrogen peroxide caused oxidative stress in chicken chicks in a significant way through a significant increase in the concentration of malondialdehyde and a significant decrease in the concentration of glutathione. In addition, giving gabapentin increased this effect in stressed chicken chicks compared to normal chickens. Giving gabapentin resulted in a significant increase in the neurotransmitter kappa while keeping the concentration of glutamate close to the negative control group, while hydrogen peroxide caused an increase in the concentration of both the neurotransmitters kappa and glutamate. In addition, giving gabapentin and hydrogen peroxide worked together to significantly increase both kappa and glutamate. We conclude from this study that oxidative stress induced by hydrogen peroxide in chicken chicks led to an increase in the pharmacological effectiveness of gabapentin, in addition to the occurrence of harmful toxic effects at the level of neurotransmitters and antioxidants.